Childhood Obesity Associates Haemodynamic and Vascular Changes That Result in Increased Central Aortic Pressure with Augmented Incident and Reflected Wave Components, without Changes in Peripheral Amplification - Juan M. Castro; Victoria García-Espinosa; Santiago Curcio; Maite Arana; Pedro Chiesa; Gustavo Giachetto; Yanina Zócalo; Daniel Bia (International Journal of Vascular Medicine)
The aims were to determine if childhood obesity is associated with increased central aortic blood pressure (BP) and to characterize haemodynamic and vascular changes associated with BP changes in obese children and adolescents by means of analyzing changes in cardiac output (stroke volume, SV), arterial stiffness (aortic pulse wave velocity, PWV), peripheral vascular resistances (PVR), and net and relative contributions of reflected waves to the aortic pulse wave amplitude. We included 117 subjects (mean/range age: 10 (5–15) years, 49 females), who were obese (OB) or had normal weight (NW). Peripheral and central aortic BP, PWV, and pulse wave-derived parameters (augmentation index, amplitude of forward and backward components) were measured with tonometry (SphygmoCor) and oscillometry (Mobil-O-Graph). With independence of the presence of dyslipidemia, hypertension, or sedentarism, the aortic systolic and pulse BP were higher in OB than in NW subjects. The increase in central BP could not be explained by the elevation in the relative contribution of reflections to the aortic pressure wave and higher PVR or by an augmented peripheral reflection coefficient. Instead, the rise in central BP could be explained by an increase in the amplitude of both incident and reflect wave components associated to augmented SV and/or PWV.